2010
DOI: 10.1111/j.1365-2893.2009.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care risk factors among women and personal behaviours among men explain the high prevalence of hepatitis C virus infection in Karachi, Pakistan

Abstract: To estimate the prevalence and identify factors associated with hepatitis C virus (HCV) infection among men and women in Karachi, Pakistan. We conducted a cross-sectional study of adult men and women in a peri-urban community of Karachi (Jam Kandah). Households were selected through systematic sampling from within all villages in the study area. All available adults within each household were interviewed about potential HCV risk factors. A blood specimen was collected to test for anti-HCV antibodies by enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
6
45
1
Order By: Relevance
“…This seroprevalence is significantly lower than that found by ZahraouiMahadji et al in Casablanca (5%) [2] and among barbers elsewhere [11,17]. Individuals giving or receiving traditional barber services have been shown to be at higher risk of HCV in most, but not all, settings [6,7,10,12,19]. In spite of the poor hygiene conditions in many barbershops in this study, we observed a near-universal practice of changing of blades between clients.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This seroprevalence is significantly lower than that found by ZahraouiMahadji et al in Casablanca (5%) [2] and among barbers elsewhere [11,17]. Individuals giving or receiving traditional barber services have been shown to be at higher risk of HCV in most, but not all, settings [6,7,10,12,19]. In spite of the poor hygiene conditions in many barbershops in this study, we observed a near-universal practice of changing of blades between clients.…”
Section: Discussioncontrasting
confidence: 61%
“…However, adults are still at risk for both HBV and HCV. In particular, acquisition and transmission of bloodborne pathogens has been shown to be an occupational risk among traditional barbers in many countries [6][7][8][9][10][11][12]. In Morocco, barbers are commonly exposed inadvertently to the blood and body fluids of their customers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…High rate of medical injection use (13 injections/person/year) and frequent reuse of injection equipment (20-60%) that involves equipment manipulation increases the risk of SIs [Janjua et al, 2005]. Sharps are more likely to be contaminated with BBPs given the high prevalence of HBV and HCV among general population (range 0.3-31.9%) [Ali et al, 2009;Janjua et al, 2010a]. Thus, the risk of a SI is high and likelihood of acquiring a BBP after a SI is also high among FLCF workers in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 82 % of administered injections in Asia were considered unnecessary [107]. Reuse of needles and reuse of syringes remain a common practice in Bangladesh and Pakistan [108,109]. Unsafe injections have been estimated to transmit 2.3-4.7 million HCV infections every year [110].…”
Section: Prevention In Healthcare Settingsmentioning
confidence: 99%